1989
DOI: 10.1002/j.1556-6676.1989.tb01360.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Cognitive Functioning of Bulimic Women

Abstract: The present study examined differences in selected areas of cognitive functioning of 18 bulimic and 23 nonbulimic women. The participants were compared on variables related to cognitive and behavioral coping and self-efficacy. Our results indicated differences between bulimic and nonbulimic women on all measures. Bulimic women demonstrated higher levels of dietary restraint; lower self-appraised problem-solving ability; lower sense of personal efficacy with regard to successful performance in a variety of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Specifically, two studies examined U.S. women who were clinically diagnosed according to DSM-III and DSM-III-R diagnostic criteria (American Psychiatric Association, 1987) as having an eating disorder. Etringer, Altmaier, and Bowers (1989) found bulimic women to have statistically significant higher PSI scores (PSI Total and all three factors) than a nonbulimic control group. Soukup, Beiler, and Terrell (1990) found both bulimic and anorexic women (as opposed to those women without an eating disorder) to have statistically higher PSI scores on the PSI Total and specifically on the Problem-Solving Confidence and Approach-Avoidance Style factors.…”
Section: Eating Disordersmentioning
confidence: 74%
“…Specifically, two studies examined U.S. women who were clinically diagnosed according to DSM-III and DSM-III-R diagnostic criteria (American Psychiatric Association, 1987) as having an eating disorder. Etringer, Altmaier, and Bowers (1989) found bulimic women to have statistically significant higher PSI scores (PSI Total and all three factors) than a nonbulimic control group. Soukup, Beiler, and Terrell (1990) found both bulimic and anorexic women (as opposed to those women without an eating disorder) to have statistically higher PSI scores on the PSI Total and specifically on the Problem-Solving Confidence and Approach-Avoidance Style factors.…”
Section: Eating Disordersmentioning
confidence: 74%
“…These consistencies with the hopelessness theory are related to the first component of hopelessness, the pervasive expectation of negative outcomes. This component gains direct support from Etringer, Altmaier & Bowers (1989), who found that bulimics had a significantly lower generalized expectancy of success than controls.…”
Section: The Hopelessness Hypothesismentioning
confidence: 76%
“…Additional empirical work supports the relationship between general self-efficacy and bulimic behavior (Bennett, Spoth, & Borgen, 1991;Cooley & Toray, 1996;Etringer, Altmaier, & Bowers, 1989;Gormally, Black, Daston, & Rardin, 1982;Mizes, 1988;Shisslak et al, 1990;Striegel-Moore, Silberstein, Frensch, & Rodin, 1989). Mizes found that helplessness, a concept related to low self-efficacy, related strongly to bulimic symptoms.…”
Section: Introductionmentioning
confidence: 83%
“…Mizes found that helplessness, a concept related to low self-efficacy, related strongly to bulimic symptoms. Similarly, Etringer et al (1989) found that women with bulimia had a much lower sense of general efficacy, including less confidence in problem-solving capacities, than nonbulimic women. In their 7-month longitudinal study of female college freshmen, Cooley and Toray (1996) found that individuals who reported more bulimic symptoms reported more feelings of ineffectiveness concurrently and that ineffectiveness predicted an increase in bulimic symptomatology.…”
Section: Introductionmentioning
confidence: 93%